Species composition and seasonal abundance of sandflies (Diptera: Psychodidae: Phlebotominae) in coffee agroecosystems - Pérez, Jeanneth; Virgen, Armando; Rojas, Julio Cesar; Rebollar Téllez, Eduardo Alfonso; Alfredo, Castillo; Infante, Francisco; Mikery, Oscar; Marina, Carlos Felix; Ibáñez Bernal, Sergio (2014)
The composition and seasonal occurrence of sandflies were investigated in coffee agroecosystems in the Soconusco region of Chiapas, Mexico. Insect sampling was performed on three plantations located at different altitudes: Finca Guadalupe Zajú [1,000 m above sea level (a.s.l.)], Finca Argovia (613 m a.s.l.) and Teotihuacán del Valle (429 m a.s.l.). Sandflies were sampled monthly from August 2007-July 2008 using three sampling methods: Shannon traps, CDC miniature light traps and Disney traps. Sampling was conducted for 3 h during three consecutive nights, beginning at sunset. A total of 4,387 sandflies were collected during the course of the study: 2,718 individuals in Finca Guadalupe Zajú, 605 in Finca Argovia and 1,064 in Teotihuacán del Valle. The Shannon traps captured 94.3% of the total sandflies, while the CDC light traps and Disney traps captured 4.9% and 0.8%, respectively. More females than males were collected at all sites. While the number of sandflies captured was positively correlated with temperature and relative humidity, a negative correlation was observed between sandfly numbers and rainfall. Five species of sandflies were captured: Lutzomyia cruciata, Lutzomyia texana, Lutzomyia ovallesi, Lutzomyia cratifer/ undulata and Brumptomyia sp. Lu. cruciata, constituting 98.8% of the total, was the most abundant species. None of the captured sandflies was infected with Leishmania spp.